Contextual Qur'anic Studies through Phenomenology: An Analysis of Ninian Smart’s Dimensions of Religion - Nida Husna Abdul Malik; Rifki Rosyad (UIN Sunan Gunung Djati Bandung, 2026)
This article examines the application of the phenomenological approach to religion, particularly Ninian Smart's seven-dimensional model, in the context of the Qur’an. The study aims to explore how these dimensions ritual, narrative, doctrinal, ethical/legal, social, emotional, and material are represented in the Qur’anic text and to assess their relevance for contemporary interpretive methodologies. Using a qualitative-descriptive method and thematic analysis of relevant verses, the findings reveal that the Qur’an encompasses all seven religious dimensions. This suggests that the Qur’an not only conveys theological doctrines and legal injunctions but also constructs a multifaceted structure of religious experience. The article highlights the strengths of Smart’s approach in bridging divine revelation with lived religious realities, while also cautioning against the epistemological risks of reducing revelation to mere subjective experience. These insights offer new avenues for developing thematic Qur’anic exegesis and multidimensional Islamic education.